Evaluation of Developed Alumni Information Management System (AIMS) Using ISO 25010:2015 - Jornadal, Mary Llourane Faith; Forca, Adrian Jaleco; Rama Putra, Gustian (Universitas Teknokrat Indonesia, 2025)
This study evaluated the Alumni Information Management System (AIMS) developed to enhance alumni tracking, career services, and institutional engagement, utilizing the ISO/IEC 25010:2015 software quality model. The evaluation focused on key characteristics: functionality, usability, reliability, performance efficiency, security, maintainability, and portability, to assess the system's effectiveness. An Iterative Software Development Life Cycle (SDLC) was employed during the development phase, allowing for incremental improvements and incorporating user feedback. Evaluation was conducted using a researcher-designed instrument aligned with the ISO/IEC 25010:2015 standard. The results indicate that the AIMS received a